Kajian atas Pelaksanaan Pengadaan Tanah untuk Kepentingan Umum: Studi Pembangunan Pembangkit Tenaga Listrik PLTA Upper Cisokan Pump Storage 1040 MW - Supriyono Supriyono (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2012)
Implementation of land acquisition for public interest is a phenomenon we oftensee today in the media-print and electronic media. One provision of land for publicpurposes is the construction of power plants. Development of the electricity sector aims topromote the welfare and intellectual life of the people to realize the ideals of the nation,to create a just and prosperous society and unseen evenly throughout the archipelago.Electricity Law No. 30 Year 2009 In Article 27 asserts that the Permit HolderPower Provider reserves the right to use the land for public use in the electricity sector. inthe implementation of electricity development obstacles and barriers both in terms oflocation determination permit the project land acquisition and the relocation of the landaffected by the electricity development plan. Delays in the process of licensing theselocations because the local government found because PLN is not a government agency.While the relocation of people due to the inhibition of indemnity still require negotiationwith the local Land Acquisition Committee.